Pengaruh Diameter Pipa Primer Pada Irigasi Tetes Bertingkat - Negara, I Dewa Gede Jaya; Hartana, Hartana; Supriyadi, Anid; Saadi, Yusron; Yasa, I Wayan; Julio, Ryan Bagus (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2024)
Multilevel drip irrigation is an irrigation method that supports water-saving agricultural activities in limited areas by channeling water through perforated pipes from emitters. An ideal multilevel drip irrigation system can provide the same volume of droplets to plants, so that the distribution of irrigation water and the uniformity of drip irrigation are important factors that need to be considered when using drip irrigation to provide plant irrigation. This research aims to determine the effect of using variations in the diameter of PVC pipes as primary pipes on the distribution of drip irrigation and its uniformity. The primary irrigation network tested for each network to the 1st floor to the 3rd floor consists of ½", ¾" diameter and 1" pipe, while the secondary and lateral drip pipe networks use ½" PVC. The test was carried out on an area of 4 m x 1 m x 1.8 m with a distance between levels of around 0.9 m, with an irrigation water source from a 200 liter tank placed on a tower with a height of 2.5 m.The results of the research show that the discharge produced by the main pipe is different on each floor of the irrigation network, on the 1st floor the discharge is 127.13 cm3/second and on the 3rd floor the discharge is 120.91 cm3/second, while on the 2nd floor the discharge is between the values of the 1st floor discharge. and 3rd floor. Regarding the results of the distribution of drip irrigation water volume, it is known that the average does not show significant differences due to differences in network operations or due to differences in pipe diameters used, where the values for floors 1 to 3 are respectively 68.75 ml, 68 .47ml, 68.19ml. The uniformity of drip irrigation shows results above 94% on all network floors and is considered very good.